Staatlich eingetragene religiöse Bekenntnisgemeinschaften in Österreich - Bair, Johann; Rees, Wilhelm (Religion und Staat im Brennpunkt, 2018)
With the federal law on the legal personality of religious denominations (10.1.1998), the category of state-registered denominations in Austria was created in addition to the category of state-recognized religious communities in Austria. The volume contains contributions from a conference at the University of Innsbruck and others, in which the state-registered religious denominations in Austria introduce themselves and at the same time state their expectations of the relationship with the state, i.e. the Republic of Austria. Also printed are the legal foundations of these religious communities.